2004
DOI: 10.1186/ar1462
|View full text |Cite
|
Sign up to set email alerts
|

MMP-3 expression and release by rheumatoid arthritis fibroblast-like synoviocytes induced with a bacterial ligand of integrin α5β1

Abstract: Fibroblast-like synoviocytes (FLSs) play a major role in the pathogenesis of rheumatoid arthritis (RA) by secreting effector molecules that promote inflammation and joint destruction. How these cells become and remain activated is still elusive. Both genetic and environmental factors probably play a role in transforming FLSs into inflammatory matrix-degrading cells. As bacterial products have been detected in the joint and shown to trigger joint inflammation, this study was undertaken to investigate whether a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…More importantly, the findings revealed that up-regulation of miR-101-3p and down-regulation of PTGS2 led to diminished proliferation, migration, and invasion of FLSs, coupled with accelerated apoptosis. Accumulating studies have proved the association of FLSs with the pathogenesis of RA through producing effector molecules, thereby expediting the inflammation and joint damage [38,39]. Resistance to apoptosis of FLSs in RA is common in the inflamed joint as a prominent characteristic [9].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the findings revealed that up-regulation of miR-101-3p and down-regulation of PTGS2 led to diminished proliferation, migration, and invasion of FLSs, coupled with accelerated apoptosis. Accumulating studies have proved the association of FLSs with the pathogenesis of RA through producing effector molecules, thereby expediting the inflammation and joint damage [38,39]. Resistance to apoptosis of FLSs in RA is common in the inflamed joint as a prominent characteristic [9].…”
Section: Discussionmentioning
confidence: 99%
“…Houseman et al found that MMP-3 and anti-cyclic citrullinated peptide (anti-CCP) antibodies were strongly predictive of joint damage in patients with RA [ 5 ]. In addition, it was previously reported that MMP-3 levels in the synovium of patients with RA were significantly elevated; moreover, the gene that encodes MMP-3 was found to be overexpressed in the synovium [ 6 ]. These data suggest that MMP-3 is a biomarker of cartilage degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Integrin-linked activation of Rho GTPases mediates gene transcription, cell cycle progression and adhesion [ 13 , 15 ]. Previous studies have demonstrated that integrin blockade can inhibit fibroblast invasion and adhesion of cells to the extracellular matrix (ECM) [ 16 , 17 ]. In particular, blockade of α2β1 integrin in RA protects against cartilage destruction via reduction of matrix metalloproteinase (MMP)-3 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%